2015
DOI: 10.4155/fso.15.87
|View full text |Cite
|
Sign up to set email alerts
|

Germline Genetic Profiling in Prostate Cancer: Latest Developments and Potential Clinical Applications

Abstract: Familial and twin studies have demonstrated a significant inherited component to prostate cancer predisposition. Genome wide association studies have shown that there are 100 single nucleotide polymorphisms which have been associated with the development of prostate cancer. This review aims to discuss the scientific methods used to identify these susceptibility loci. It will also examine the current clinical utility of these loci, which include the development of risk models as well as predicting treatment eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 136 publications
(121 reference statements)
0
11
0
Order By: Relevance
“…SNPs, which are variations in DNA sequences when a single nucleotide differs between members of related strands, are the most common genetic variants in the human genome . SNPs occur randomly throughout the genome and are found more frequently in non‐coding regions of DNA.…”
Section: Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…SNPs, which are variations in DNA sequences when a single nucleotide differs between members of related strands, are the most common genetic variants in the human genome . SNPs occur randomly throughout the genome and are found more frequently in non‐coding regions of DNA.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In the middle of the 2000s, the genome‐wide association study, a large case–control study, was carried out; a new method of genetic variant discovery was sequentially ascertained. The genome‐wide association study has identified >100 published PCa SNPs . A large multiethnic genome‐wide association study including 7783 cases and 38 595 controls (80.3% non‐Hispanic white, 4.9% African American, 7.0% East Asian and 7.8% Latino) showed that the aggregate risk scores combining information across all 105 known SNPs were significant in all ethnic groups, but the magnitude of this association varied substantially by ethnicity possibly because of different frequencies of risk alleles, especially in East Asians and African Americans .…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…As yet there is no standard guidance for mainstreaming genomic testing into the prostate cancer diagnostic pathway, however, there is huge potential, with approximately 58% of prostate cancer cases thought to be caused by a germline genetic predisposition. 19 Information from germline genetic testing related to the risk of aggressive disease and treatment outcomes can be combined with genetic analysis of tumours at the time of diagnosis to generate a personalised treatment pathway. Identifying men with prostate cancer who also have a germline gene mutation will identify potential therapeutic targets that may be effective in managing their disease.…”
Section: Prostate Cancermentioning
confidence: 99%